Technological innovations of the digital age in the sports industry and the law - Ροζάκης, Παναγιώτης-Αλέξανδρος (Πανεπιστήμιο Πελοποννήσου, 2022)
This thesis aims to examine a number of applications of innovative digital technologies in the sports industry and the subsequent legal issues that have arisen from their imple-mentation. Technology has greatly affected the development and growth of sports in many areas both on and outside of the field. This influence has only increased with the emergence of new digital applications and their introduction into the sports industry. The applications of financial technology (FinTech) to a wide range of traditional sectors of the sports industry and the interaction they have with other emerging technologies, affect, shape, and change the way sports are played, viewed, experienced and regulated. Chapter I will be composed of the technical definitions of the relevant digital technolo-gies including examples from their integration into various fields to give the reader a better understanding of the technical terms. In Chapter II will be reviewed the effect of FinTech in the sports industry and will be a presentation of a case study of smart con-tracts, tokenization of sports memorabilia, non-fungible tokens (NFTs), socios, fan to-kens and cryptocurrencies and also the interaction of fintech tools with big data and data protection regulations. Finally, the Epilogue comprises concluding remarks about all the previously mentioned and provides thoughts for further investigation.
Τεχνολογικές καινοτομίες της ψηφιακής εποχής στην αθλητική βιομηχανία και το δίκαιο
Keywords: Χρηματοοικονομική τεχνολογία; Τεχνολογικές καινοτομίες - Δίκαιο και νομοθεσία; Αθλητικό δίκαιο; Κρυπτογραφία; Financial technology; Technological innovations - Law and legislation; Sports law; Cryptography; Χρηματοοικονομική τεχνολογία; Αθλητικό δίκαιο; Αλυσίδα κατανεμημένης εγγραφής; Κρυπτογραφία; Προστασία δεδομένων; Fintech; Blockchain; NFTs; Sports Law; Data